A flexible and multifunctional metal–organic framework as a matrix for analysis of small molecules using laser desorption/ionization mass spectrometry. Issue 48 (28th May 2019) - Ma, Wen; Xu, Shuting; Ai, Wanpeng; Lin, Cheng; Bai, Yu; Liu, Huwei
Abstract : Fast screening of multi-functional MOFs as SALDI-MS matrices for the detection of small molecules and simultaneous enrichment and detection of analytes. Abstract : A variety of functional metal–organic frameworks (MOFs) were prepared via a universal method and served as matrices in small molecule analysis using laser desorption/ionization mass spectrometry. Among them, cysteine-MOF was found to be a multifunctional composite as an excellent matrix and an efficient adsorbent for N -glycans due to its high hydrophilicity, low background interference and unique size-exclusion effect.